Religion and Culture of Origin. Re-Shaping Identity in the Integration Process: A Case Study in Sicily - Ferrante, Lorenzo (Qualitative Sociology Review, 2019)
What happens when people of different cultures, values, religion live together? Sociological studies on immigrative phenomenon often swing between immigration and integration policies. These policies actually reveal the difficulty of the host society to institutionalize new models of social differences accompanying multiculturalism. Immigrants who “arrive” continue their life in a place where they do not passively participate in the passing of time, but become actors. Pressed by the hegemonic culture of the host society to adapt, do not cease to practice their religious and origin cultural expressions, often in conditions of urban spatial and social marginalization, they resist assimilation with ethnic persistence strategies. Considering the impact of religion and origin cultural values on expression of differences, it is important to consider their role in the integration process. And, above all—facilitate or hinder integration? These dynamics have been analyzed in a research study on immigrants’ integration process in Palermo. The main results are presented in this paper. In this case study, the research’s data hypothesizes a theoretical model of integration in which immigrants, free to express their religious and cultural differences, tend to reduce their perception of minority